2021
DOI: 10.23917/jramathedu.v6i4.14093
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate basic sciences and engineering students’ understanding of the concept of derivative

Abstract: Derivative is one of the most important topics in calculus that has many applications in various sciences. However, according to the research, students do not have a deep understanding of the concept of derivative and they often have misconceptions. The present study aimed to investigate undergraduate basic sciences and engineering students’ understanding of the concept of derivative at Tehran universities on based the framework of Zandieh. The method was descriptive-survey. The population included all undergr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…In another view of understanding, Rodríguez-Nieto et al ( 2021b) state that quality level 0 mathematical connections (with mathematical errors or inconsistencies) are the causes for which students have difficulty understanding the derivative concept and quality level 2 mathematical connections (based on mathematically consistent arguments) are a guarantee of understanding by students or teachers. Haghjoo and Reyhani (2021) concluded that university students have inadequate understanding of the derivative concept in contexts (numerical, physical, verbal and graphic), for example, they state that the inconsistency between interpretations of slope in mathematic classes (involving difference quotient limit, velocity, rate of change, etc.) and interpretations of rate of change in engineering classes may cause some problems for students in understanding the derivative, additionally, they share similar results with previous research in two directions:…”
Section: Research Problems About Derivative's Understandingmentioning
confidence: 99%
“…In another view of understanding, Rodríguez-Nieto et al ( 2021b) state that quality level 0 mathematical connections (with mathematical errors or inconsistencies) are the causes for which students have difficulty understanding the derivative concept and quality level 2 mathematical connections (based on mathematically consistent arguments) are a guarantee of understanding by students or teachers. Haghjoo and Reyhani (2021) concluded that university students have inadequate understanding of the derivative concept in contexts (numerical, physical, verbal and graphic), for example, they state that the inconsistency between interpretations of slope in mathematic classes (involving difference quotient limit, velocity, rate of change, etc.) and interpretations of rate of change in engineering classes may cause some problems for students in understanding the derivative, additionally, they share similar results with previous research in two directions:…”
Section: Research Problems About Derivative's Understandingmentioning
confidence: 99%